Melanins and melanogenesis: methods, standards, protocols. (21st June 2013) - d'Ischia, Marco; Wakamatsu, Kazumasa; Napolitano, Alessandra; Briganti, Stefania; Garcia‐Borron, José‐Carlos; Kovacs, Daniela; Meredith, Paul; Pezzella, Alessandro; Picardo, Mauro; Sarna, Tadeusz; Simon, John D.; Ito, Shosuke
Summary: Despite considerable advances in the past decade, melanin research still suffers from the lack of universally accepted and shared nomenclature, methodologies, and structural models. This paper stems from the joint efforts of chemists, biochemists, physicists, biologists, and physicians with recognized and consolidated expertise in the field of melanins and melanogenesis, who critically reviewed and experimentally revisited methods, standards, and protocols to provide for the first time a consensus set of recommended procedures to be adopted and shared by researchers involved in pigment cell research. The aim of the paper was to define an unprecedented frame of reference built on cutting‐edge knowledge and state‐of‐the‐art methodology, to enable reliable comparison of results among laboratories and new progress in the field based on standardized methods and shared information.